Antibacterial Edible Coating from Mandarin Orange Peel (Citrus reticulata) and Moringa Leaf (Moringa oleifera) Extract for Fish Preservation - Maulidan Firdaus; Desy Nila Rahmana; Diah Fitri Carolina; Nisrina Rahma Firdausi; Zulfaa Afiifah; Berlian Ayu Rismawati Sugiarto (Jurnal Riset Kimia, 2023)
Approximately 10% of total fish production is wasted due to decomposition. Excessive formalin use in fish preservation can be potentially lethal. One of the natural preservatives is edible coating, which can be prepared from natural ingredients such as mandarin orange peel (Citrus reticulata) pectin and Moringa leaves (Moringa oleifera) which contain antibacterial compounds. The purpose of this research was to examine the antibacterial influence of edible coatings made from pectin of mandarin orange peel with the addition of Moringa leaf extract and to determine its effect on the freshness of nile tilapia (Oreochromis niloticus). Moringa leaf extraction was performed using the Soxhlet extraction method with 96% ethanol at 60–80 °C, while the mandarin orange peel was isolated by reflux using 1% HCl with a pH of 1.5 for 4 hours at 90 °C. Edible coating was synthesized from mandarin orange peel pectin and carboxymethyl cellulose (CMC) which was homogenized with distilled water, and glycerol was added as a plasticizer. Edible coatings were prepared with various concentrations of 0%, 50%, and 100% Moringa leaf extract. Nile tilapia with the addition of edible coatings experienced slower decay, especially in the variations of 100% Moringa leaf extract. This was evidenced by the quantitative test through the Total Plate Count (TPC) test which still did not exceed the limit of >5.6 log CFU/g.